Oral Neutrophils Characterized: Chemotactic, Phagocytic, and Neutrophil Extracellular Trap (NET) Formation Properties - Moonen, Carolyn G. J.; Hirschfeld, Josefine; Cheng, Lili; Chapple, Iain L. C.; Loos, Bruno G.; Nicu, Elena A. (Frontiers in Immunology, 2019)
Maintenance of oral health is in part managed by the immune-surveillance and antimicrobial functions of polymorphonuclear leukocytes (PMNs), which migrate from the circulatory system through the oral mucosal tissues as oral PMNs (oPMNs). In any microorganism-rich ecosystem, such as the oral cavity, PMNs migrate towards various exogenous chemoattractants, phagocytose bacteria and produce neutrophil extracellular traps (NETs) to immobilize and eliminate pathogens. PMNs obtained from the circulation through venipuncture (hereafter called cPMNs) have been widely studied using various functional assays. We aimed to study the potential of oPMNs in maintaining oral health and therefore compared their chemotactic and antimicrobial functions with cPMNs. To establish chemotactic, phagocytic and NET forming capacities, oPMNs and cPMNs were isolated from healthy subjects without obvious oral inflammation. Directional chemotaxis towards the chemoattractant fMLP was analyzed using an Insall chamber and video microscopy. fMLP expression was assessed by flow cytometry. Phagocytosis was analyzed by flow cytometry, following PMN incubation with heat-inactivated FITC-labelled micro-organisms. Furthermore, agar plate-based killing assays were performed with Escherichia coli (Ec). NET formation by oPMNs and cPMNs was quantified fluorimetrically using SYTOX™ Green, following stimulation with either PMA or RPMI medium (unstimulated control). In contrast to cPMNs, the chemotactic responses of oPMNs to fMLP did not differ from controls (mean velocity ± SEM of cPMNs: 0.79 ± 0.24; of oPMNs; 0.10 ± 0.07 micrometer/min). The impaired directional movement towards fMLP by oPMNs was explained by significantly lower fMLP receptor expression. Increased adhesion and internalization of various micro-organisms by oPMNs was observed. oPMNs formed 13 times more NETs than stimulated cPMNs, in both unstimulated and stimulated conditions. Compared to cPMNs, oPMNs showed a limited ability for intracellular killing of Ec. In conclusion, oPMNs showed exhausted capacity for efficient chemotaxis towards fMLP which may be the result of migration through the oral tissues into the oral cavity, being a highly “hostile” ecosystem. Overall, oPMNs’ behavior is consistent with hyperactivity and frustrated killing. Nevertheless, oPMNs most likely contribute to maintaining a balanced oral ecosystem, as their ability to internalize microbes in conjunction with their abundant NET production remains after entering the oral cavity.